State Anxiety Subjective Imbalance and Handicap in Vestibular Schwannoma - Saman, Yougan; Mclellan, Lucie; Mckenna, Laurence; Dutia, Mayank B.; Obholzer, Rupert; Libby, Gerald; Gleeson, Michael; Bamiou, Doris-Eva (Frontiers in Neurology, 2016)
ABSTRACT Evidence is emerging of a significant clinical and neuro-anatomical relationship between balance and anxiety. Research has suggested a potentially priming effect with anxiety symptoms predicting a worsening of balance function in patients with underlying balance dysfunction. We propose to show that a vestibular stimulus is responsible for an increase in state anxiety and there is a relationship between increased state anxiety and worsening balance function. Aims 1. To quantify state anxiety following a vestibular stimulus in patients with a chronic vestibular deficit. 2. To determine if state anxiety during a vestibular stimulus would correlate with the severity of chronic balance symptoms and handicap. Methods Two separate cohorts Vestibular Schwannoma (VS) patients underwent vestibular tests (electronystagmography, cervical and ocular vestibular evoked myogenic potentials and caloric responses) and questionnaire assessment (Vertigo handicap Questionnaire, Vertigo Symptom Scale, State Trait Anxiety Inventory)Fifteen post resection Vestibular schwannoma patients, with complete unilateral vestibular deafferentation, were assessed at a minimum of 6 months after surgery in Experiment 1 (Aim 1). Forty-five patients with VS in-situ and with preserved vestibular function formed the cohort for Experiment 2 (Aim 2). Experiment 1: VS subjects (N=15) with a complete post-resection unilateral vestibular deafferentation completed a State anxiety questionnaire before caloric assessment and again afterwards with the point of maximal vertigo as the reference (Aim 1). Experiment 2: State anxiety measured at the point of maximal vertigo following a caloric assessment was compared between two groups of presenting with balance symptoms (Group 1 N=26) and without balance symptoms (Group 2 N=11) (Aim 2). The presence of balance symptoms was defined as having a positive score on the VSS-VER. Results In experiment 1, a significant difference (p<0.01) was found when comparing state anxiety (STAI-Y1) at baseline and at the peak of the subjective vertiginous response in post resection patients with a unilateral vestibular deafferentation. In experiment 2, VS in-situ patients with balance symptoms had significantly worse state anxiety at the peak vertiginous response than patients without balance symptoms (p<0.001), as did patients with a balance related handicap (p<0.001). Conclusion Anxiety symptoms during a vestibular stimulus may contribute to a priming effect